Soil Quality Assessment Under Different Land-Use and Litter Conditions in Agrarian Landscape - Zaidan, Imelda Nasywa; Muhammad Hafidz Al Farid; Gigih Firman Prabowo; Indana Zulfa Anisa; Intan Nirmala Sari; Ridho Damar Mas Adi Wijaya; Bagus Setiabudi Wiwoho; Rudi Hartono (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2025)
Abstract: Dayurejo Village, on the slopes of Mount Arjuno, is an agrarian landscape where diverse land uses—teak stands, agroforestry, banana and coffee plantations, and production forest—compete for space and shape soil conditions. This study assesses soil quality under different litter conditions and interprets the findings in relation to land functions and village-level spatial planning. Using a quantitative descriptive approach, soil samples were collected from topsoil (0–30 cm) and subsoil (30–60 cm) in five land-use types and analyzed for texture, porosity, pH, and organic matter. Rudi Hartono nic C, while litter thickness, pH, and moisture were also measured. Results indicate that all land uses are characterized by acidic soils with very low organic C (<0.60%) and litter layers that are generally dry, limiting decomposition. Agroforestry and forest land maintain relatively high porosity and thick litter, supporting their role as hydrological protection and buffer zones, whereas banana, coffee, and teak areas exhibit compaction and degradation, requiring targeted rehabilitation. The study concludes that integrating soil-quality indicators into village zoning and agrarian management is essential for sustainable land and spatial planning in Dayurejo Village. Keywords: Agrarian landscape, Land Use, Soil quality, Spatial planning